2000
DOI: 10.1177/0164027500222005
|View full text |Cite
|
Sign up to set email alerts
|

“Friendship” Interactions and Expression of Agitation among Residents of a Dementia Care Unit

Abstract: Friendships" (ongoing interpersonal interactions) and agitated behavior were studied among 59 residents of a dementia special care unit; most residents had mild to moderate cognitive impairment. Behavior scan data were recorded by trained observers over six months. Three scans per hour were conducted, seven days a week, between 9 a.m. and 9 p.m., producing more than 17,000 observations. A marginal model for binary longitudinal data was developed to associate covariates with repeated observations of agitation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…After all, it is more likely that there is more common ground and shared mutual interests between fellow residents of a similar age and with similar generational experiences, compared to staff members. Research has shown that good quality residentresident relations are associated with a better sense of well-being for residents with dementia (Clare et al, 2008) and also with lower levels of agitation (Kutner, Brown, Stavisky, Clark, & Green, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…After all, it is more likely that there is more common ground and shared mutual interests between fellow residents of a similar age and with similar generational experiences, compared to staff members. Research has shown that good quality residentresident relations are associated with a better sense of well-being for residents with dementia (Clare et al, 2008) and also with lower levels of agitation (Kutner, Brown, Stavisky, Clark, & Green, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1 We argue that practitioners have a role to play in creating the opportunities for such relationships to develop while cautioning against relying upon too narrow or simplistic a notion of what constitutes friendship. For instance, Kutner, Brown, Stavisky, Clark, and Green (2000) who set out to explore friendship interactions and expressions of agitation among residents with dementia in care homes, defined friendships as: '. .…”
Section: Introductionmentioning
confidence: 99%
“…1 More specifically, verbal and physical agitation have been directly correlated with understimulation in this population. 2–4 In long-term care settings, problem behaviors were shown to increase when the person was inactive and to decrease when structured activities were offered. 5 …”
mentioning
confidence: 99%